2009
DOI: 10.1002/humu.20976
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype analysis in 2,405 patients with a dystrophinopathy using the UMD-DMD database: a model of nationwide knowledgebase

Abstract: UMD-DMD France is a knowledgebase developed through a multicenter academic effort to provide an up-to-date resource of curated information covering all identified mutations in patients with a dystrophinopathy. The current release includes 2,411 entries consisting in 2,084 independent mutational events identified in 2,046 male patients and 38 expressing females, which corresponds to an estimated number of 39 people per million with a genetic diagnosis of dystrophinopathy in France. Mutations consist in 1,404 la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
265
8
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 311 publications
(335 citation statements)
references
References 68 publications
45
265
8
17
Order By: Relevance
“…Compared with the large French UMD-DMD database (2405 patients), 54% of DMD gene deletions in our study are not significantly different from the 61% reported in DMD patients (P ¼ 0.55). 39 In all, 79% of these deletions start in the distal hot spot (exons 44-55), as observed in the UMD-DMD database (74%). We report a similar proportion of duplications (15% of our carriers versus 13% in DMD patients) and of point mutations (27% in our series versus 26%).…”
Section: Muscle Study and Protein Expression In The Musclementioning
confidence: 60%
See 1 more Smart Citation
“…Compared with the large French UMD-DMD database (2405 patients), 54% of DMD gene deletions in our study are not significantly different from the 61% reported in DMD patients (P ¼ 0.55). 39 In all, 79% of these deletions start in the distal hot spot (exons 44-55), as observed in the UMD-DMD database (74%). We report a similar proportion of duplications (15% of our carriers versus 13% in DMD patients) and of point mutations (27% in our series versus 26%).…”
Section: Muscle Study and Protein Expression In The Musclementioning
confidence: 60%
“…Interestingly, we found a significant difference concerning the occurrence of de novo deletions, which represent 25% of the de novo mutations versus 71% in the UMD-DMD database (P ¼ 0.01). 39 Even if we do not know the parental origin of the de novo events, this lower proportion of de novo deletions compared with de novo point mutations in female carriers could be explained by the possible paternal origin of new mutations, which cannot be observed in DMD boys.…”
Section: Muscle Study and Protein Expression In The Musclementioning
confidence: 92%
“…In fact, CGA to TGA transitions comprised nearly a quarter of nonsense mutations (18/69 cases; Table 1). This is because the CpG site is vulnerable to deamination, in which C is replaced by T. 28,29 The CGA codon is found 29 times in the dystrophin gene, and 12 of them (41%) were found to be mutated to TGA in this study. Although nonsense mutations usually cause DMD, three nonsense mutations were identified in the milder, BMD cases (4%) ( Table 1).…”
Section: Nonsense Mutationsmentioning
confidence: 66%
“…Based on the data available in the clinical and molecular databases maintained in our laboratory, 1 we selected 50 patients' DNA from previously collected 550 non-related DMD/BMD families (French Ministry of Health, collection ID: DC-2008-417) dividing them into three groups (Table 1; Supplementary Table 1). All patients provided an agreement for further analysis on informed consent form.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…There is no simple relationship between the type or the size of the mutations in the DMD gene and the severity of phenotype, but the reading-frame rule holds true for 96% of Duchenne Muscular Dystrophy (DMD; OMIM#310200) and 93% of Becker Muscular Dystrophy (BMD; OMIM#300376) cases. 1 As the majority of mutations in DMD are large deletions and duplications, several dosage-sensitive quantitative methods mainly focused on discovering mutations in the coding regions of the gene are commonly used. 2 Here we describe the introduction into the current diagnostic practice and validation of a high-resolution custom-designed Comparative Genomic Hybridization array (array-CGH) enabling to interrogate the entire 2.2 Mb genomic region of the DMD gene for copy number variations.…”
Section: Introductionmentioning
confidence: 99%